Coagulation and adsorption techniques for purification of the amalgamation slurry waste - Mohammad Nurcholis; E Nursanto; H E B Sakti; D F Yudiantoro; D Haryanto (Journal of Degraded and Mining Lands Management, 2020)
Amalgamation in the processing of community gold mines may leave slurry waste with the potential for heavy metal contamination of the environment. Technical studies for handling these wastes are very necessary to process the waste using a simple and applicable manner in the community. The purpose of this study was to examine the coagulation-adsorption technique of liquid waste from the amalgamation process. Slurry waste samples from the amalgamation process were collected from amalgamation sites in Boto Village, Wonogiri regency which had the highest Hg and Pb levels in the slurry. The coagulation-adsorption process is carried out by a continuous process with the gravitational flow because the area of the amalgamation process has a steep slope.  Coagulation of particles in the slurry used two kinds of natural ingredients, i.e. papaya seed, and moringa seed extracts.  The adsorption was conducted using two types of minerals, i.e. Ca-bentonite and zeolite which had been activated. The results of this study showed that the coagulation process was a simple process to purify amalgamation slurry waste and reduce the levels of Fe, Mn, Hg, and Pb metals.  Then the following step by using the absorption process to produce clear water from amalgamation liquid waste and reduce the levels of Fe and Mn metals. Coagulation using papaya seeds might purify amalgamation slurry waste and reduce heavy metal content of Fe 99.996%; Mn 99.994%; Pb 100%; Hg 100%. Based on these results, the Hg and Pb metals were metals that were very easy to settle. Adsorption on the liquid result of the coagulation process using unactivated zeolite reduced the metal content of Fe> 99.40% and Mn> 88.69%.